Evaluation of the biocompatibility of the dialyzer membrane in dogs with acute kidney injury induced by gentamicin treated by hemodialysis (Research, Society and Development, 2021)
The dialysis procedures as hemodialysis (HD) try to keep the patient with acute kidney injury (AKI) alive until kidney regeneration. This paper evaluates the biocompatibility of cellulose acetate and polysulfone membranes in healthy dogs and in AIK ones submited to hemodialyses, analyzing biological parameters and clinical signs presented in this procedure. The hemodialysis animals were divided in four groups (each one with 8 dogs): group 1 composed by healthy animals that used cellulose acetate membrane; group 2 constituted by dogs with AKI that used cellulose acetate membrane; group 3 formed by healthy animals that used polysulfone membrane; group 4 composed by dogs with AKI that used polysulfone membrane. AKI induction was made by applying gentamicin (45mg/kg/EV/day). The main change was related to weight loss of the animals in the groups with AKI. There was also a significant reduction in urea and creatinine levels, mainly in hemodialysis animals with polysulfone membrane, while sodium, potassium and glucose levels did not show significant differences between the groups. The C3´s and microglobulin b2 levels didn´t present significant changes in the groups, while the TNFa was in high levels in AKI´s groups hemodialysed with polysulfone and cellulose acetate membranes, with higher level found in the last one. It didn´t have significant changes related to arterial blood pressure and others hematologial parameters. It is possible conclude that there was an increase in TNFa level from AKI´s dogs submitted to hemodialyses, and polysulfone membrane was slightly more biocompatible than cellulose acetate membrane, however more markers should be tested.